Intangible Cultural Capital and Mosque-Based Entrepreneurship - Sebayang, Asnita Frida; Hayati, Fitroh; Haryatiningsih, Ria; Fathia, Yolanda Dienul; Pratiwi, Syahrani Cantika (KnE Social Sciences, 2023)
This study was conducted at the Jogokariyan Mosque in Jogjakarta, Indonesia, which already has a popular mosque program. The mosque management plays a crucial role in promoting the economic capacity of the surrounding area. One of the flagship programs aimed at improving the local economy is called Masjidpreneur, which focuses on mosque-based entrepreneurship. The objective of this study is to identify the behavioral factors that drive the success of the mosque program. The research method utilized is quantitative descriptive, employing a Likert Scale for self-assessment of both mosque managers and mosque entrepreneurship partners (community members). A comparison of the self-assessment results between mosque managers and mosque partners indicates a convergence of perspectives, with a high level of agreement in the assessment results. Both parties possess several intangible cultural capitals, including a strong commitment to honesty, striving to practice the teachings of Islam in daily behavior, zero tolerance for fraudulent acts, feeling restless when unable to convey the truth, and a strong desire to carry out their responsibilities to the best of their ability. They also look to Prophet Muhammad SAW as an example in their daily lives, exhibiting various attitudes that reflect the strength of intangible cultural capital. The average assessment score obtained is 5.42 out of a scale of 6, indicating that the behavior of mosque economic managers tends to be highly commendable. This finding highlights that the key to the mosque program’s success lies not only in the management of funds but also in the strength of intangible cultural capital. Keywords: mosque, entrepreneurship, cultural capital, economic development, local economy